DETERMINING HEAT LOSSES FROM THE BUILDING ENVELOPE USING THE NON-STATIONARY METHOD - Nodar KEVKHISHVILI; Tengiz JISHKARIANI; Nikoloz JAVSHANASHVILI (World Science, 2023)
One of the main causes of the climate change is accumulation of huge amount of carbon dioxide (CO2) in the atmosphere emitted from the combusting of organic fuels (coal, oil products and natural gas), consequently, to slow down the  progress of the global warming is directly related to the limitation of CO2 emission which could be achieved through the rational use of fuel and energy in every sector (industrial, household, transport and building sectors), introduction of energy-saving measures including highly efficient technologies and innovative methods. The building sector accounts for about 40% of the energy saving potential, therefore reduction of energy losses is the best way to reduce energy consumption of buildings. To calculate the heat loss from the building envelope, it is necessary to know the thermal conductivity coefficient (λ) of each construction element. Currently developed methods of λ determination are entirely based on the laboratory test using the stationary regime. For more realistic results, it is necessary to take into account the daily variability of temperature and non-stationary thermal conductivity processes. Solving the non-stationary thermal conductivity tasks are associated with the significant difficulties due to the application of the relatively complex mathematical equations. Usually, the theory of non-stationary thermal conductivity refers to the method of separation of variables or the so-called Laplace Transform, which requires the use of operational counting methods. The article presents an innovative method for determining the coefficient of thermal conductivity (λ) of each construction element in the non-stationary temperature regime, which enables determination of heat losses from the building envelope in real environment using the precise definition of thermal flow velocity.